Hubungan Berat Badan Lahir Bayi Dengan Kejadian Ruptur Perineum Pada Persalinan Pervaginam - Dewi, Ida Ayu Dhian Permana; Rahayu, Sri; Budiani, Ni Nyoman (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2025)
Postpartum hemorrhage constitutes 40% of the predominant etiologies of maternal mortality in Indonesia. Perineal lacerations precipitate secondary hemorrhaging. The weight of the neonate may influence the second stage of labor. An increase in fetal weight correlates with an elevated risk of perineal laceration. The objective of this study was to examine the correlation between neonatal birth weight and the prevalence of perineal lacerations during vaginal delivery at the Bali Royal General Hospital in 2023. This investigation employed a correlation analytical research design utilizing a cross-sectional approach. A total sample of 256 participants was obtained through comprehensive sampling. Secondary data were extracted from the electronic medical record system (e-RM). Data analysis was conducted using Spearman's rank correlation coefficient. The findings indicated that the majority of perineal lacerations were classified as grade 2, affecting 196 individuals (79.4%), with the predominant occurrence in the normal birth weight category, which encompassed 234 subjects (94.7%). Notably, the majority of infants with normal birth weight experienced grade 2 lacerations, amounting to 192 individuals (98%), while infants born with higher weights exhibited grade 3 lacerations, totaling 11 individuals (78.6%), thus indicating a significant association with the incidence of perineal lacerations during vaginal delivery. It is imperative for expectant mothers to ensure the maintenance of fetal weight to avert excessive neonatal birth weight.